Thin Ferromagnetic Films Deposition by Facing Target Sputtering Method - Iljinas, A.; Dudonis, J.; Bručas, R.; Meškauskas, A. (Nonlinear Analysis: Modelling and Control, 2005)
Facing targets sputtering system, constructed specially for ferromagnetic cathode sputtering, was investigated in this study. The currentvoltage (I-V ) characteristics, deposition rate dependence on the discharge power, dependence on the distance between the center axis of targets and substrate, and on distance between the targets were investigated. Magnetic field distribution between two targets was measured. FTS system has been used successfully to prepare Fe films on glass substrate in various temperatures. The highest deposition rate for this film was 2.2 nm/s when distance between targets was 70 mm and the distance between substrate and a distance from the center axis of targets was 60 mm. X-ray diffraction (XRD) and Atomic Force Microscope (AFM) were used to analyze the surface structure of Fe thin films. It was found that films crystallite sizes depend on deposition temperature.